Interpolation Theorems for Nonlinear Urysohn Integral Operators in General Morrey-Type Spaces - Burenkov, Victor; Nursultanov, Erlan (Eurasian Mathematical Journal, 2020)
In this paper, we present new interpolation theorems for nonlinear Urysohn integral operators. In particular, interpolation theorems of Marcinkiewicz–Calderon type and Stein–Weiss–Peetre type are obtained.